Anterior Spinal Artery Syndrome Following Coronary Artery Bypass Grafting: a Case Report - Mirhosseini,Seyed Mohsen (2017)
Abstract We present a patient with unstable angina candidate for coronary artery bypass grafting. Saphenous vein graft was used in obtuse marginal and left internal mammary artery to left anterior descending artery properly. After surgery, the patient experienced flaccid paralysis of lower limb and impaired sensation of touch and warmth of knee and below. A computed tomography angiogram of lower limbs and thoracolumbar magnetic resonance imaging showed no abnormality. Based on the symptom, clinical diagnosis of anterior spinal artery syndrome was considered. The artery of Adamkiewicz is an important supplier to the anterior spinal artery. Internal thoracic mammary artery, used in coronary artery bypass grafting, is suspected as a collateral supplier of the artery of Adamkiewicz and has been accused for cause of spinal infarction.